2000
DOI: 10.1046/j.1442-2026.2000.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of serious injuries caused by stairway falls

Abstract: Objective: To study the demographics of patients who sustained serious injuries from falling down stairs. Method: This study is a retrospective analysis of all patients who presented to an urban hospital with an injury severity score of equal to or greater than 16 after falling down stairs during the period January 1992 to December 1996. Patient demographics, stair location and number, severity and anatomical nature of injuries, serum ethanol levels, patient referral characteristics and mortality rates were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Patients most at risk from this mechanism are either older patients or younger people who are intoxicated, each scenario providing unique diagnostic and management challenges. 1 5 Older patients are more likely to have significant injuries despite a low risk mechanism, while the presence of comorbidities increases their risk of mortality despite a lower injury severity. 6 Intoxicated patients also provide a diagnostic challenge, as physical examination is often unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…Patients most at risk from this mechanism are either older patients or younger people who are intoxicated, each scenario providing unique diagnostic and management challenges. 1 5 Older patients are more likely to have significant injuries despite a low risk mechanism, while the presence of comorbidities increases their risk of mortality despite a lower injury severity. 6 Intoxicated patients also provide a diagnostic challenge, as physical examination is often unreliable.…”
Section: Introductionmentioning
confidence: 99%
“…Subanalyses were conducted on humerus and femur fractures. NEISS categories for type of injury were regrouped into (1) dislocations, (2) fractures, (3) closed head injuries (including concussions and intracranial hemorrhages), (4) soft tissue injuries (including sprains, strains, hematomas, and contusions), (5) lacerations (including puncture wounds), and (6) miscellaneous. Disposition from the ED was categorized as (1) released (patients who were treated and released or left the ED without treatment) or (2) hospitalized (patients who were admitted, transferred to another hospital, or held for observation).…”
Section: Study Variablesmentioning
confidence: 99%
“…Although there is extensive literature on stair-related injuries as a major cause of mortality and morbidity among older adults, [1][2][3][4] little has been published on stair-related injuries among young children. An emergency department (ED)-based study showed that stairs were among the top 10 causes of injury to children aged ,1 year during each month of life and that the incidence of those injuries rose as infant mobility increased, with stairs being the most common cause of injury at 12 months of age.…”
mentioning
confidence: 99%
“…Substance effects have been linked to a variety of fall types due to their ability to impair an individual's thinking and balance and thus cause them to jump or slip/trip 65 . The types of falls with substance-affected cases in this study are predominantly high falls, which have also commonly been associated with individuals who suicide from heights 5,7 , however they are not strongly associated with falls down stairs as previously documented 16,17,66 . This suggests there are other means of impaired balance, such as physical conditions, that are potentially a greater risk contributor for stair falls in Victorian residents.…”
Section: Behavioursmentioning
confidence: 62%